The Effect of Ethanol Extract of Sweet Leaf (Sauropus androgynus (L.) Merr.) to The Mortality of Aedes aegypti L. Larvae - Mahendra, Anton Giri; Haryati, Sri; Sakiman, FX. Bambang Sukilarso (Nexus Kedokteran Translasional, 2016)
Introduction: Sweet leaf (Sauropus androgynus (L.) Merr.) is known to contain saponins, tannins and flavonoids. Saponins, tannins and flavonoids are compounds that known as larvicides. This study aims to determine whether the ethanol extract of the sweet leaf (Sauropus androgynus (L.) Merr.) had an effect on mortality of larvae of Aedes aegypti L. Methods: This research were laboratory experimental design with post test only control group design. The object was the larva of Aedes aegypti L. that divided into 7 groups, each group contains 25 larvae. Each group consists of four plastic cups filled with ethanol extract of sweet leaf at the same concentration. The control group were exposed to ethanol extract of the sweet leaf with a concentration of 0 mg / 100 ml. The other six groups were given different number of ethanol extract of sweet leaf. There were 200 mg/ 100 ml, 600 mg/ 100 ml, 1000 mg/ 100 ml, 1400 mg/ 100 ml, 1800 mg/ 100 ml, 2200 mg/ 100 ml, respectively. The observation was taken at the next 24 hours and the number of dead larvae were counted. Linear regression and probit regression were used as statistical analysis. Results: Linear Regression test shows that the R2 score was 0.99. That means the percentage of ethanol extract of sweet leaf (Sauropus androgynus (L.) Merr.) to kill larvae was 99 % and the rest 1% was affected by other variables. Probit regression test shows LC50 was 1157 mg / 100 ml and LC99 was 3075 mg / 100 ml. Conclusion: Ethanol extract of sweet leaf (Sauropus androgynus (L.) Merr.) had an effect on mortality of larvae of Aedes aegypti L. on LC50 of 1157 mg / 100ml and LC99 of 3075 mg / 100 ml, as well as the percentage of variable effect of ethanol extract of sweet leaf (Sauropus androgynus (L.) Merr.) on mortality of Aedes aegypti L. larvae at 99%. Keywords: sweet leaf (Sauropus androgynus (L.) Merr.), Aedes aegypti L. larvaeÂ